MANAJEMEN KOMUNIKASI EFEKTIF ANTARA BIDAN, PASIEN, DAN KELUARGA - Sefentina Sefentina; Santi Widya Purba; May Linda Kristina (Jurnal Minfo Polgan, 2024)
Communication is at the heart of quality midwifery care. Effective interactions between midwives, patients (mothers), and family members are the foundation for building trust, ensuring understanding of health information, facilitating shared decision-making, and ultimately improving satisfaction and health outcomes. However, various barriers can hinder effective communication in the clinical setting. This literature review examines the importance of effective communication, the challenges faced, and strategies for improving communication management between midwives, patients, and families. The aim is to provide insight into how communication skills can be improved to support patient- and family-centered midwifery care and promote positive pregnancy, labor, and postpartum experiences.